The health system approach to the complementary and alternative medicine - Alireza Azargoon; Mohammad Zibaei (Journal of Research & Health, 2015)
Since different nations have emphasized reusing their traditional methods in medicine over the last two decades, and the World Health Organization’s recent approach has also focused on restoring traditional medicine in different parts of the world, those methods that are more compatible with the popular culture of a country should be considered. In our country, the traditional medicine, with its rich resources and scientific support as well as its considerable compatibility with the health orders of Islam, and the recommendations of the Holy Prophet and Imams, has been regarded by scientists and people for a long time. Using Iranian traditional medicine and the rich and valuable treasures of this precious heritage has useful and researchable issues in order to enrich human knowledge and scientific advances, and to open new windows into the field of medicine. To be expanded, the traditional medicine needs to be organized, its education has to be centralized, and its educational content should be based on scientific documents and evidence so that academic communities could be satisfied and possible misuses in the field of complementary and traditional medicine could be prevented. Establishing the secretariat of the complementary and traditional medicine educational council in the Ministry of Health, medicinal herbs center, and traditional medicine school seems to be an effective measure to institutionalize and organize theses sciences in Iran. Necessary planning to employ the essential and efficient staff can be one of the important duties of this secretariat, and it can be operational by compiling educational planning for MSc and PhD courses on traditional medicine. The aim of this major is to train specialists familiar with popular principles and methods of prevention, treatment, education, and applicable researches in Iranian traditional medicine. Consequently, in addition to using the newest information of the classical medicine, this method can be used to provide, restore, and promote health in patients and societies when its application is useful for them and it promotes human knowledge. Ultimately, the three factors affecting organization and development include compiling the curriculum and teaching these sciences in universities considering academic standards, extracting results based on researches and reliable documents and evidences, and informing academic communities clearly, properly, and precisely.